Newly discovered stone age site of Ulaan khanan : : a techno-typological study from the surface collection - Tsedendorj, Bolorbat; Dashzeveg, Bazargur; Guunii, Lkhundev (Studia Archaeologica, 2024)
The Kherlen River, which headwaters from the mountains of Khan Khentii, streams through the territory of three provinces of Mongolia: Khentii, Tuv, and Dornod. Most of the archaeological sites found in its basin exhibit characteristics of the Neolithic period, and mainly consist of in situ stone tools dispersed on the surface. The mixing of prehistoric artifacts from different periods in a certain place is undoubtedly related to the unique climatic conditions of Mongolia and the geology of the Kherlen River basin. In this article, we discuss the site of Ulaan Khanan, located about 21 km south of the Kherlen River in the Bayankhutag soum area of Khentii Province. The stone artifacts from this site are suggested as belonging to two different periods: The Paleolithic and Neolithic. The Paleolithic artifacts include points, scrapers, retouched blades, and different types of lithic blanks (mainly blades and flakes). Conversely, the Neolithic artifacts conform to knapping methods involving the reduction of narrow-faced and wedge-shaped cores, including a single micro-core as well as polyhedral and cylindrical cores. The lithic assemblage(s) described here consists of a few tool types, such as points, scrapers, burins, combination tools, and retouched blades, and show evidence of reduction sequences primarily aimed at blade and flake production.